HOMOLOGOUS SEX CHROMOSOMES IN THREE DEEPLY DIVERGENT ANURAN SPECIES. (30th May 2013) - Brelsford, Alan; Stöck, Matthias; Betto‐Colliard, Caroline; Dubey, Sylvain; Dufresnes, Christophe; Jourdan‐Pineau, Hélène; Rodrigues, Nicolas; Savary, Romain; Sermier, Roberto; Perrin, Nicolas
Abstract : Comparative genomic studies are revealing that, in sharp contrast with the strong stability found in birds and mammals, sex determination mechanisms are surprisingly labile in cold‐blooded vertebrates, with frequent transitions between different pairs of sex chromosomes. It was recently suggested that, in context of this high turnover, some chromosome pairs might be more likely than others to be co‐opted as sex chromosomes. Empirical support, however, is still very limited. Here we show that sex‐linked markers from three highly divergent groups of anurans map to Xenopus tropicalis scaffold 1, a large part of which is homologous to the avian sex chromosome. Accordingly, the bird sex determination gene DMRT1, known to play a key role in sex differentiation across many animal lineages, is sex linked in all three groups. Our data provide strong support for the idea that some chromosome pairs are more likely than others to be co‐opted as sex chromosomes because they harbor key genes from the sex determination pathway.